2022
DOI: 10.1088/1742-6596/2265/2/022057
|View full text |Cite
|
Sign up to set email alerts
|

Physics informed DMD for periodic Dynamic Induction Control of Wind Farms

Abstract: Dynamic Induction Control (DIC) is a novel, exciting branch of Wind Farm Control. It makes use of time-varying control inputs to increase wake mixing, and consequently improve the velocity recovery rate of the flow and the power production of downstream turbines. The Pulse and the Helix are two promising DIC strategies that rely on sinusoidal excitations of the collective pitch and individual pitch of the blades, respectively. While their beneficial effects are evident in simulations and wind tunnel tests, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Muscari et al. (2022) conducted a dynamic mode decomposition of a wake of a turbine with the helix approach and find that helicoidal shapes at the frequency of the excitation and its harmonics are the dominant modes of the wake. Furthermore, the authors report, in contrast to Frederik et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscari et al. (2022) conducted a dynamic mode decomposition of a wake of a turbine with the helix approach and find that helicoidal shapes at the frequency of the excitation and its harmonics are the dominant modes of the wake. Furthermore, the authors report, in contrast to Frederik et al.…”
Section: Introductionmentioning
confidence: 99%
“…Axial induction control reduces the induction of upstream turbines, such that downstream turbines can produce more power; see, for example, Nilsson et al (2015). Some studies also combine these two strategies (Bossanyi 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the default pitch rate limits of the IEA-15 MW turbine have to be increased if β > 4 • in order to enable helix pitch actuation. All helix cases in this study use the most common helix actuation frequency of St = 0.25, but we do note that there is still uncertainty not only in the optimal amplitude but also frequency [8]. Note that the helix is only implemented for the upstream turbine (denoted as T1).…”
Section: Turbine Simulationsmentioning
confidence: 99%
“…For the initial proof of concept, the frequency is derived from DIC as St = 0.25 and the influence of the amplitude is analyzed for two levels [6]. A study for a single amplitude, but four different Strouhal numbers suggested that the optimal frequency might deviate from St = 0.25, although only considering uniform inflow [8]. In [9] reinforcement learning was applied to optimize the helix amplitude for a three-turbine wind farm (St = 0.25) reporting an overall power gain of 6.8%.…”
Section: Introductionmentioning
confidence: 99%